2008
DOI: 10.1007/s10657-008-9059-5
|View full text |Cite
|
Sign up to set email alerts
|

Why football players may benefit from the ‘shadow of the transfer system’

Abstract: Labour contracts, Transfer restrictions, Transfer fees, Bosman and Monti transfer system, FIFA regulations, D86, J49, L83,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…Moreover, team managers (principals), who are primarily in charge of negotiations, often earn less than their best paid players (agents), which is unlikely to be the case in "classical" principal-agent situations. Furthermore, players face higher risks by future uncertainty related to injuries and shortened career duration (Dietl, Franck, and Lang 2008;Frick 2007). Summing up, differences between the basketball industry and other industries of course exist.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, team managers (principals), who are primarily in charge of negotiations, often earn less than their best paid players (agents), which is unlikely to be the case in "classical" principal-agent situations. Furthermore, players face higher risks by future uncertainty related to injuries and shortened career duration (Dietl, Franck, and Lang 2008;Frick 2007). Summing up, differences between the basketball industry and other industries of course exist.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the third hypothesis, the particular structure of the basketball labor market gives rise to three comments. First, we assume the firm to be risk neutral, which is in line with past sports economic studies (Dietl, Franck, and Lang ; Robinson et al ; Scully , ; Szymanski ). We believe that this is a very reasonable assumption for the NBA.…”
Section: The Modelmentioning
confidence: 92%
“…For example, salary caps (Késenne, 2000b;Rathke, 2009, 2011), transfer restrictions (Dietl, Franck, and Lang, 2008b) and centralized marketing by league monopolies (Falconieri, Palomino, Sakovics, 2004) would not be tolerated in other industries. These exceptions result in very interesting labor market peculiarities within professional team sports.…”
Section: Introductionmentioning
confidence: 99%
“…It is found that the transfer fee is different in various segments in English professional football sports [1], and the determination of transfer fee is sim- (a) e-mail: wxzhou@ecust.edu.cn ilar in both professional and nonleague football sports [2]. Usually football players benefit from the transfer system [3]; However the transfer system might also obstruct the free movement of football players between Member States in Europe and may restrict the ability of most clubs to compete for elite players [4]. It is also found that in the English Football League there is no racial difference in footballers' transfer prices [5].…”
mentioning
confidence: 99%